(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The Arab region is located at the crossroads of the continents of Africa, Asia and Europe, and has historically witnessed waves of refugees, and the movement of refugees is one of the most important factors driving economic and social change in the region. Asylum has a significant negative impact on economic and social development sectors, such as health, urban development, youth development and gender relations. To identify the positive effects of migration and mitigate its potential negative impacts, a multidimensional and multi-experienced approach is required. This study examines the concept of asylum and its types and the economic development that the phenomenon of asylum leaves on the Arab countries, including the experience of Jordan, which in turn affects all other variables in this country, the most important of which are the political, social and other aspects. The results of the study found that the refugee phenomenon witnessed by Jordan has negatively affected its economic development.